Efektivitas Brain Gym pada Anak Prasekolah dalam Meningkatkan Konsentrasi - Syuhrotut Taufiqoh (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Concentration of learning is a factor that determines a person’s success, either studying in class, in study groups, or studying independently. The low concentration of a person in learning can cause a decrease in a person's learning outcomes. Several methods can be used to increase concentration in children. One of them is Brain Gym. Brain Gym is a series of simple movements that are fun and maximize the overall brain that is applied to students to improve student learning abilities. Brain Gym can maximize learning potential and reduce stress levels.  This study aims to analyze the effect of Brain Gym on the concentration of preschool children in a Early Childhood Education at Takal Health Center.Methods:   This study uses a quantitative type of research in the form of a quasi-experimental. The research design used Pre and Posttest group design. The sampling technique in this study was purposive sampling, so 14 samples were obtained. The research instrument used the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) observation sheet.Results:   The results of statistical tests using Wilcoxon (P-value = 0.000 <0.05) means that it shows that there is an influence of Brain Gym (brain exercise) on concentration in preschool-aged children in a Early Childhood Education at Takal Health Center.Conclusion:   Brain Gym can increase concentration in preschool children in a Early Childhood Education at Takal Health Center.